The Influence of Government Fiscal policy Toward Economy Development - Rizki Ananda, Fajar; Norita; Tito Andriansyah (ASIAN PUBLISHER, 2023)
Fiscal policy is a strategy set by government institutions to regulate the structure of taxes and government spending to solve economic problems. In a country, the government formulates this policy to focus on the country's economic stability, such as reducing poverty. From an Islamic economic perspective, the role of the state is to obtain equal and fair income and wealth to protect the stability of economic development that comes to improve people's lives. Therefore, this article will examine in detail the impact of government fiscal policy on and whether the fiscal policy will improve or worsen the Indonesian economy in the future.